THE METHOD OF PRODUCTION OF BIMETALLIC DISKS STEEL-ALUMINIUM BRONZE - V. A. Zemtsov; D. A. Meshkov; I. O. Sazonenko (Литьë и металлургия, 2008)
The technology of the slug production and ways of elimination of possible shrink defects is stated in details in the article. It is offered to use face disks of bimetallic slugs steel-aluminium bronze.